Kajian Peraturan Perlindungan Konsumen Di Sektor Perbankan - Nurdin, Aad Rusyad (Jurnal Hukum & Pembangunan, 2018)
The dynamics of carrying out intensive banking business activities between customers and banks have the potential to raise various problems that cause violations of the rights of customers as consumers of a bank's business activities. To overcome the problems of customers as banking consumers, it is necessary to examine the regulations in the banking sector regarding consumer protection regulations in the banking sector with Law No. 8 of 1999 concerning Consumer Protection (UUPK). This research is a normative research that study the law of consumer protection as contained in the UUPK. The results of the study show that the legislation in the banking sector in general is in accordance with the regulation on consumer protection as regulated in the UUPK So that the regulation of consumer protection in the banking sector can be used as a benchmarking for the development of the development of consumer protection in other sectors, and also be an input into changes in the UUPK.